THE MOBILIZATION APPROACHES OF MEDIA LITERACY FOR CHILDREN AND YOUNGSTERS IN FOREIGN COUNTRIES, AND THE APPROACHES FOR THAILAND - ครุจิต, วรัชญ์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2019)
This study has two objectives as follows: 1) to study mobilization approaches to develop media and digital literacy for children and youngsters in foreign countries, and 2) to study mobilization approaches to develop media and digital literacy for children and youngsters in Thailand. This study is a qualitative research, employing document research method to study mobilization approaches for developing media and digital literacy of six projects in six foreign countries; 1) The United States: The News Literacy Project (NLP), 2) Canada: The Ontario Media Literacy Curriculum, 3) The European Union: European Association for Viewers Interests (EAVI), 4) India: The Peace Gong Media Literacy Programme, 5) Australia: SeeMe Media Literacy Project, 6) Japan: Digital Storytelling (DST) for Media Literacy The study found five key findings that can be applied as mobilization approaches to develop media and digital literacy for children and youngsters in Thailand; 1) having support from all of the relevant stakeholders, 2)designing content with clear direction that correspond with key problems of the country, 3) producing knowledge and research studies in the field of media literacy or having support from knowledgeable organizations, 4) transferring of knowledge that leads to action of creating media content with experts as mentors, and 5) having continuous, modern, and various media content and activities. From this finding, researcher has developed the 3E4I Model, which comprises of Education, Experience, Expert, Interconnectedness, Information, Information and Integration.